BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Correction to: The proteorhodopsins of the dinoflagellate Oxyrrhis marina: ultrastructure and localization by immunofluorescence light microscopy and immunoelectron microscopy - Erhard Rhiel; Martin Westermann; Frank Steiniger; Christian Hoischen (Protoplasma, 2021)

The proteorhodopsins of the dinoflagellate Oxyrrhis marina: ultrastructure and localization by immunofluorescence light microscopy and immunoelectron microscopy - Erhard Rhiel; Martin Westermann; Frank Steiniger; Christian Hoischen (Protoplasma, 2020)
At least 7 proteorhodopsin sequences of Oxyrrhis marina were recently proven in bands obtained by sucrose density gradient centrifugation, and MS analyses revealed that the bands consisted almost of pure, native proteorhodopsins (Rhiel et al. 2020). The proteorhodopsin fractions, i.e., bands B2, B3, and B4 were subjected to transmission electron microscopy. Negative staining revealed that band B2 consisted most likely of monomeric/oligomeric proteorhodopsins with particle dimensions of about 6 nm. Negative staining, freeze-fracture, and cryo-transmission electron microscopy revealed that bands B3 and B4 consisted of vesicular, sheet-like, and cup-shaped structures which all seemed to be composed of protein. Frequently, ring-like protein aggregates were registered at higher magnifications. They measured about 4 nm in diameter with a tiny hole of 1.5 nm in the middle. The bands B2, B3, and B4 were pooled and used to raise an antiserum. Immunoelectron microscopy resulted in intense labeling of the isolated structures. Immunofluorescence light microscopy of formaldehyde-fixed Oxyrrhis cells resulted in intense labeling of the cell periphery. Some cell internal structures became labeled, too. Immunoelectron microscopy of freeze-fractured cells revealed that most likely the membranes of the amphiesmal vesicles were labeled at the cell periphery, while the cell internal label seemed to originate from the food vacuoles.

The HDAC6/8/10 inhibitor TH34 induces DNA damage-mediated cell death in human high-grade neuroblastoma cell lines - Fiona R. Kolbinger; Emily Koeneke; Johannes Ridinger; Tino Heimburg; Michael Müller; Theresa Bayer; Wolfgang Sippl; Manfred Jung; Nikolas Gunkel; Aubry K. Miller; Frank Westermann; Olaf Witt; et al. (Archives of Toxicology, 2018)

Isolation and characterisation of the trichocysts of the dinophyte Prorocentrum micans - Martin Westermann; Frank Steiniger; Nils Gülzow; Helmut Hillebrand; Erhard Rhiel (Protoplasma, 2015)

Isolation and characterization of the ejectisomes of the prasinophyte Pyramimonas grossii - Erhard Rhiel; Martin Westermann; Frank Steiniger; Christian Kirchhoff (Protoplasma, 2013)

The shape of caveolae is omega-like after glutaraldehyde fixation and cup-like after cryofixation - Wiebke Schlörmann; Frank Steiniger; Walter Richter; Roland Kaufmann; Gerd Hause; Cornelius Lemke; Martin Westermann (Histochemistry and Cell Biology, 2010)

Improved antigen retrieval in freeze-fracture cytochemistry by evaporation of carbon as first replication layer - Wiebke Schlörmann; Markus John; Frank Steiniger; Martin Westermann; Walter Richter (Histochemistry and Cell Biology, 2007)

Belt-like localisation of caveolin in deep caveolae and its re-distribution after cholesterol depletion - Martin Westermann; Frank Steiniger; Walter Richter (Histochemistry and Cell Biology, 2005)